Integrated Optics Structures On Sol-Gel Derived Organic-Inorganic Hybrids For Optical Communications - André, Paulo
Organic-inorganic hybrid materials are a technologically key class of advanced multifunctional materials that fulfil the challenging strict requirements of the beginning of the century: higher levels of sophistication, miniaturisation, recyclability, reliability and low energy consumption with potential to be used as low-cost components in optical networks operating at high bit rates. In this work, high-rejection optical filters (19 dB) first-order Bragg gratings inscribed in channel waveguides written in thin films of sol-gel derived organic-inorganic hybrid based on methacrylic acid modified zirconium tetrapropoxide, Zr(OPr(n))(4), (so-called di-ureasils), using UV-laser direct-write method.